Forging Meaningful Pathways: Synergies for Sustainable Tourism Resilience in Challenging Times - Subadra, I Nengah (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
This editorial synthesizes key insights through the lens of Arlt’s Meaningful Tourism (MT) paradigm, which addresses sustainability fatigue by prioritizing simultaneous well-being for all six stakeholders: visitors, communities, employees, businesses, governments, and the environment. Research highlights five imperatives for resilience in an era of converging crises: (1) Holistic Stakeholder Alignment via transparent MT metrics; (2) Community Empowerment through models like upscale homestays (Dam) and blue-economy conservation; (3) Deep Experiences fulfilling meaning-seeking through spiritual tourism, music events, and emotional engagement; (4) Strategic Enablers like digital inspiration, workforce education, and management systems; and (5) Collaborative Governance to tackle infrastructure, equity, and environmental challenges. The volume advocates for integrated action aligning interests, centering communities, curating authenticity, leveraging technology, and fostering partnerships to transform tourism into a resilient force for shared prosperity and cultural-environmental vitality.